The Prognostic Value of Pretherapy Peripheral Blood Inflammatory Indices in Myelodysplastic Syndromes - Shi, Cong; Gong, Shengping; Niu, Tingting; Li, Tongyu; Wu, An; Zheng, Xiaojiao; Yang, Shujun; Ouyang, Guifang; Mu, Qitian (Frontiers in Oncology, 2022)
Background: Inflammation appears to have a critical role in carcinogenesis tumor growth according to emerging research. The platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and plasma C-reactive protein (CRP) are considered to reflect the systemic inflammatory response and clinical prognosis. The prognostic value of inflammatory indices in myelodysplastic syndrome (MDS) patients remains unclear. Methods: 213 MDS patients were enrolled for study. Univariate and multivariate analyses were performed to determine the prognostic significance of various markers, including PLR, NLR and CRP. Results: MDS patients with higher PLR, NLR, CRP had significantly shorter overall survival (OS, P = 0.002, P = 0.019, P < 0.0001). Based on univariate analysis, age (≥ 60 years), gender (male), lower hemoglobin level (< 10 g/dl), higher bone marrow blast percentage (> 5%), poorer karyotype and higher IPSS-R score were significantly associated with shorter OS. The patients with higher CRP had shorter leukemia-free survival (LFS, P = 0.041). But high PLR and NLR had no significant influence on LFS (P > 0.05). Multivariate Cox proportional hazards regression analysis indicated that high PLR and CRP were also independent adverse prognostic factors for OS in MDS (P = 0.031, P = 0.029). Conclusions: Elevated PLR and CRP could predict poor prognosis independent of the IPSS-R and provide a novel evaluation factor for MDS patients.